Synthesis of Analogues of Thyroid Hormones: Nuclear Receptor Modulators - de Castro, Guilherme Vieira; Rocha, Carlos Murilo Romero; Sanches, Vitor Lacerda; Ribeiro, Pedro H. Zana; Donate, Paulo Marcos; de Laurentiz, Rosangela da Silva; Polikarpov, Igor; Sairre, Mirela Ines (Orbital: The Electronic Journal of Chemistry, 2015)
Thyroid hormones are essential for the development and differentiation of all cells of the human body. This work reports the synthesis of some synthetic structural analogues of thyroid hormones, which may be modulators of the thyroid hormone receptor. The known compounds GC-1 (Sobetirome) and CG-24 were successfully prepared and two novel analogous molecules were also synthesized by a new and efficient synthetic methodology.DOI: http://dx.doi.org/10.17807/orbital.v7i3.739